FACTORS THAT INFLUENCE PURCHASING DECISIONS FOR COSMETIC PRODUCTS AT GUARDIAN - Nathania, Geovanni; Arry Widodo; Anita Silvianita; Nurafni Rubiyanti (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
Indonesia's cosmetics industry has experienced significant growth in recent years, with an increase of 9.61% in 2021 and a CAGR increase of 5.81% in 2022-2027. This growth is due to the increasing demand for cosmetic products and services. Each beauty brand markets its products both online and offline. Offline, many beauty brands are capitalizing on opportunities by working with retail stores in Indonesia. This is because currently the retail industry in Indonesia is experiencing very rapid growth. one of these retail stores is Guardian. Guardian sells more than 10,000 health and beauty products. because of the many products sold at guardian, consumers are confused in determining the items they want to buy because there are many items that have the same function but different brands, so this makes it possible or many factors that influence consumers in making purchasing decisions This study was to determine the factors that influence purchasing decisions for cosmetic products at Guardian and to determine the most dominant factor in influencing purchasing decisions for cosmetic products at Guardian. By examining 14 factors, according to Kotler & Keller (2016), Kotler (2022), and Tjiptono (2017). To gather primary data, a questionnaire will be disseminated via Google Forms through social media platforms. The questionnaire will employ a Likert scale with four gradations, ranging from